2023
DOI: 10.3390/ijms24065210
|View full text |Cite
|
Sign up to set email alerts
|

Outbred Mice with Streptozotocin-Induced Diabetes Show Sex Differences in Glucose Metabolism

Abstract: Outbred mice (ICR) with different genotypes and phenotypes have been reported to be more suitable for scientific testing than inbred mice because they are more similar to humans. To investigate whether the sex and genetic background of the mice are important factors in the development of hyperglycemia, we used ICR mice and divided them into male, female, and ovariectomized female (FOVX) groups and treated them with streptozotocin (STZ) for five consecutive days to induce diabetes. Our results show that fasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Mechanistically, increased STZ resistance in female mice has been demonstrated to be related to higher oestrogen levels, with oestrogen known to suppress inflammation ( Abildgaard et al 2020 ), protect against inflammatory cytokine insult ( Sachs et al 2020 ), promote misfolded protein degradation ( Xu et al 2018 ) and enhance glucose-stimulated insulin secretion ( Tiano & Mauvais-Jarvis 2012 ). Indeed, upon ovariectomy, female mice become more susceptible to STZ with similar metabolic dysregulation as observed in male mice ( Kim et al 2023 ). In harmony with this, ovariectomised female mice treated with oestradiol present with an improved protection against the harmful effects of STZ ( Li et al 2018 ).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Mechanistically, increased STZ resistance in female mice has been demonstrated to be related to higher oestrogen levels, with oestrogen known to suppress inflammation ( Abildgaard et al 2020 ), protect against inflammatory cytokine insult ( Sachs et al 2020 ), promote misfolded protein degradation ( Xu et al 2018 ) and enhance glucose-stimulated insulin secretion ( Tiano & Mauvais-Jarvis 2012 ). Indeed, upon ovariectomy, female mice become more susceptible to STZ with similar metabolic dysregulation as observed in male mice ( Kim et al 2023 ). In harmony with this, ovariectomised female mice treated with oestradiol present with an improved protection against the harmful effects of STZ ( Li et al 2018 ).…”
Section: Discussionmentioning
confidence: 87%
“…There is a belief that female mice are more tolerant to the detrimental effects of STZ than males ( Ariza et al 2014 , Chandramouli et al 2018 , Kim et al 2020 ). In that respect, several studies have already investigated the sex-specific effects of STZ treatment in mice, with a general consensus that the diabetogen causes more detrimental effects on pancreatic islet morphology in male than female mice ( Kolb 1987 , Abildgaard et al 2020 , Kim et al 2020 , 2023 ), although this has been debated ( Plesner et al 2014 ). Mechanistically, increased STZ resistance in female mice has been demonstrated to be related to higher oestrogen levels, with oestrogen known to suppress inflammation ( Abildgaard et al 2020 ), protect against inflammatory cytokine insult ( Sachs et al 2020 ), promote misfolded protein degradation ( Xu et al 2018 ) and enhance glucose-stimulated insulin secretion ( Tiano & Mauvais-Jarvis 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we only utilized male mice. Male mice have historically been used to study effects of STZ, in large part due to the difficulty of inducing hyperglycemia in female mice [94][95][96][97][98][99]. Given the higher prevalence of depressive-like behavior in female clinical populations, it is critically important to study female models of hyperglycemia-associated depression.…”
Section: Evaluation Of Neuroinflammationmentioning
confidence: 99%
“…Additionally, females are more resistant to STZ-induced diabetes type 1, thus we must take into consideration the different stages of the disease progression in males and females. Studies have shown that females treated with the same dose of STZ have lower blood glucose levels compared to males [52] but females develop a more severe diastolic dysfunction, despite lower blood glucose levels [53].…”
Section: Plos Onementioning
confidence: 99%